1545 Topiramate is as effective as acetazolamide at lowering intracranial pressure in healthy rodents. (1st December 2017) - Scotton, William; Botfield, Hannah; Uldall, Maria; Westgate, Connar; Mitchell, James; Jensen, Rigmor; Sinclair, Alex
Abstract : Background: Management of Idiopathic Intracranial Hypertension (IIH) aims to reduce intracranial pressure (ICP). Acetazolamide is the most commonly used drug, with class 1 evidence demonstrating modest improvement in patients with mild visual loss. Other drugs used include Topiramate, Furosemide, Amiloride and Octreotide, despite little mechanistic or clinical evidence to support their use. The aim of this study was to ascertain which of these drugs has the greatest effect on lowering ICP in-vivo . Methods: Using a validated epidural ICP recording method we measured changes in ICP in conscious female rodents after subcutaneous administration of these drugs at clinically equivalent and supra-clinical doses over 2 hours (peak plasma concentrations). Results: At clinical doses, Topiramate lowered ICP by 32% (p=0.0009) compared to a 25% reduction for Acetazolamide (p=0.0081). Post-hoc analysis showed no significant difference between the two (p=0.85). Furosemide, Amiloride and Octreotide had no significant effect. Conclusion: Our in-vivo studies have demonstrated that, at clinically equivalent doses, Topiramate significantly lowers ICP and is as effective as acetazolamide. Topiramate may have additional advantages in IIH, including its migraine prevention properties and weight loss effects. These findings support the need for future randomised controlled trials evaluating the therapeutic efficacy of topiramate in IIH.